Information, social networks and emotions: fear and anger towards Pedro Sánchez 2019–2021 - José Manuel Rivera; Nieves Lagares; Erika Jaráiz; María Pereira (Frontiers in Political Science)
IntroductionThe objective of this research is to determine the relationship between the use citizens make of social networks to learn about politics and the emotions expressed towards political leaders, taking as a case study the current Prime Minister of Spain Pedro Sánchez.MethodsA quantitative methodological approach was used in this longitudinal study. This approach proposes both a descriptive and multivariate analysis of data from three databases.ResultsThe analysis of results shows important differences between consuming political information on social networks and not doing so in terms of the type of negative emotions (anger and fear) generated towards Pedro Sánchez. Connecting these findings with previous cognitive approaches led us to conclude that, while fear encourages citizens to seek alternative information, when they seek it through social networks the expression of anger increases.DiscussionIn this sense, preliminary results suggest that fear towards Pedro Sánchez becomes anger when information is proactively sought in social networks.